Market and society in Korea : interest, institution, and the textile industry - McNamara, Dennis L. (Routledge advances in Korean studies ;, 2002)
"How did industrial structures in textiles evolve in the absence of sophisticated market-supporting institutions? Assessing the roles of capital, labour, and state, Dennis McNamara discovers a distinctive style of interest bargaining to bridge uncertainties and foster entrepreneurship. The textile industry serves as a microcosm of the broader social changes of the past five decades. Dramatic transitions from family firms to professional capitalism, from state direction to regulation, and from company unions to industry federations take centre stage. Moving among executives, labour leaders, and state officials, the author charts development across the crucible of contending interests